The devil you know - Tracy, P. J. (Detective Margaret Nolan series, 2023)
"Darkness is nothing new to LAPD Detective Margaret Nolan, but in P.J. Tracy's The Devil You Know, even she isn't prepared for the scandalous deception of deadly proportions that shakes the very foundation of Hollywood and its untouchables...and leaves her entangled in its rotten core. Los Angeles has many faces: the real LA where regular people live and work, the degenerate underbelly of any big city, and the rarefied world of wealth, power, and celebrity. LAPD Detective Margaret Nolan's latest case plunges her into this insular realm of privilege, and gives her a glimpse of the decay behind the glitter. Beloved actor Evan Hobbes is found in the rubble of a Malibu rockslide, a day after a fake video ruins his career. It's not clear to Nolan if it's an accident, a suicide, or a murder, and things get murkier as the investigation expands to his luminary friends and colleagues. Meanwhile, Hobbes's agent is dealing with damage control, his psychotic boss, and a woman he's scorned"--